Fully Percutaneous Treatment of LVOT Obstruction and Mitral Regurgitation in a Patient With History of Acromegaly - Lucca Loretz, MD; Federico Moccetti, MD; Mathias Wolfrum, MD; Bart De Boeck, MD, PhD; Simon Fabian Stämpfli, MD, MSc; Matthias Bossard, MD; Adrian Attinger-Toller, MD; Yves Suter, MD; Florim Cuculi, MD; Stefan Toggweiler, MD (JACC: Case Reports, 2025)
Background: We report a 79-year-old woman with congestive heart failure. The patient had a history of acromegaly due to a pituitary macroadenoma. Case Summary: Echocardiography revealed severe mitral regurgitation due to flail of the posterior leaflet and a peak pressure gradient in the left ventricular outflow tract of 107 mm Hg due to basal septal hypertrophy. Heart catheterization revealed coronary artery disease of the left anterior descending. After heart team decision, alcohol septal ablation and concomitant percutaneous coronary intervention was performed with subsequent mitral transcatheter edge-to-edge repair (TEER), which resulted in a reduction in mitral regurgitation from severe to mild-to-moderate, reduction of left ventricular outflow tract gradient to 40 mm Hg, and reduction of mean left atrial pressure to 8 mm Hg. The patient was discharged home 2 days after mitral TEER. Discussion: In this complex scenario, we successfully performed percutaneous coronary intervention, transcoronary alcohol septal ablation (of septal hypertrophy), and mitral TEER. We are only aware of one other case of transcoronary alcohol septal ablation (of septal hypertrophy) in a patient with acromegaly. Take-Home Message: With today’s advanced interventional techniques, older patients with complex pathologies may be successfully treated with a short recovery period and early discharge.